(untitled) (Innovative professional education, 2025)
The publication deals with the essence, role and significance of the process of forming career orientations in the educational process of ІVET institutions in modern conditions. The concept of «career orientations» is considered as socially conditioned and psychologically motivated incentives of an individual to build a career, which significantly depend on the defined priorities in the system of values, socio-psychological guidelines, life experience, as well as the needs of applicants for professional (vocational-technical) and specialized pre-higher education